Toward an Understanding of Development of Learning to Solve Ill-Defined Problems in an Online Context: A Multi-Year Qualitative Exploratory Study - Peddibhotla, Naren (Online Learning, 2016)
The case study is a classic tool used in several educational programs that emphasizes solving of ill-defined problems. Though it has been used in classroom-based teaching and educators have developed a rich repertoire of methods, its use in online courses presents different challenges. To explore factors that develop skills in solving ill-defined problems, I present results of a seven-year study seeking to develop tools for facilitating and assessing skills for case studies in an online graduate class. This study began with the introduction of a classroom-based case method into an online graduate class. Over the following years, I used three sources of data to make changes to the design of the course with respect to case studies: feedback from students, feedback from colleagues, and measurement of student performance. Findings suggest the following general approaches may work better in online classes involving case studies in particular, and more broadly in courses that teach solving of ill-defined problems: 1) immersion (or the use of drills) to support trial and error learning especially given the additional distractions of an online setting as compared to attending classes on campus; 2) structure to facilitate learning as it involves building skills based on absorptive capacity that students acquire from skills learned earlier; 3) social learning to enhance trial and error learning; 4) inductive learning that may be more appropriate to online teaching as compared to deductive learning; 5) provision of structure instead of participation by the instructor may encourage self-discovery of methods to solve ill-defined problems in an online context.